Holistic primary health care for Aboriginal and Torres Strait Islander prisoners: exploring the role of Aboriginal Community Controlled Health Organisations - Simon Pettit; Paul Simpson; Jocelyn Jones; Megan Williams; M. Mofizul Islam; Anne Parkinson; Bianca Calabria; Tony Butler (Elsevier, 2019)
Abstract Objective: Aboriginal and Torres Strait Islander Community Controlled Health Organisations (ACCHOs) have been identified as having an important role in improving the health and wellbeing of individuals in prison; however, a lack of information exists on how to strengthen this role. This paper explores the experiences of ACCHO staff in primary health care to individuals inside or leaving prison. Methods: Nineteen staff from four ACCHOs were interviewed. ACCHO selection was informed by proximity to prisons, town size and/or Local Government Area offending rates. Thematic analysis of the interviews was undertaken. Results: While most ACCHOs had delivered post‐release programs, primary health care delivery to prisoners was limited. Three themes emerged: i) a lack of access to prisoners; ii) limited funding to provide services to prisoners; and iii) the need for a team approach to primary health care delivery. Conclusion: A holistic model of care underpinned by a reliable funding model (including access to certain Medicare items) and consistent access to prisoners could strengthen ACCHOs' role in primary health care delivery to people inside or leaving prison. Implications for public health: ACCHOs have an important role to play in the delivery of primary health care to prisoners. Existing models of care for prisoners should be examined to explore how this can occur.